CORRELATION OF LEARNING SELF-REGULATION WITH ACADEMIC STRESS IN FIRST-DEGREE MEDICAL STUDENTS - Bayantari, Ni Made; Budiapsari, Putu Indah; Indonesiani, Suyasning Hastiko (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Academic stress is response to academic activity in school or university especially student’s task and activity caused feelings of discomfort, tension, and changes in behaviour. Academic stress often occurs, especially in college students with a prevalence of 38-71% for college students in the world, 39.6-61.3% in Asia and in Indonesia itself, it is found that 36.7-71.6 students experience stress. As academic stress increases, self-regulation becomes important in learning. Stress and frustration can be resolved by good self-regulation and also problem solving strategies where self-regulation is a process to activate and maintain thoughts, behaviours, emotions to achieve goals. This study aimed to determine correlation of learning self-regulation with academic stress in first degree medical students.Case Discussion: this study was analytic observational with cross sectional approach design, which conducted on 156 college students. The average score of academic stress and self -regulation were 86.92 ± 7.72 and 143.55 ± 38.40; respectively, which negative significance relationship p<0.05 and r= - 0.702.Conclusion: there was negative relationship between stress academic with self-regulation good self-regulation cause lowering academic stress. It was recommended that the students should be decreased the academic stress and increase the self-regulation.